Methodical approach to define external environment friendliness level of enterprise development - Kosenko, Aleksandra; Poberezhnyi, Roman; Pantelieiev, Mykhailo; Poberezhna, Nataliia (Сумський державний університет, 2018)
The methodical approach to determining the level of environmental friendliness to the development of machine-building enterprises is proposed, which takes into account the distribution of the environment to the general and innovation-investment. The expediency of using multivariate factor analysis for the partial system substantiation and generalizing indicators of profitability is proved. The results of the study are illustrated by the example of the machine-building enterprises in Kharkiv industrial region.

Запропоновано методичний підхід до визначення рівня сприятливості зовнішнього середовища до розвитку машинобудівних підприємств, який враховує розподіл середовища на загальне та інноваційне-інвестиційне. Доведено доцільність використання багатовимірного факторного аналізу для обґрунтування системи часткових та узагальнюючого показників сприятливості. Результати дослідження проілюстровано на прикладі машинобудівних підприємств Харківського промислового регіону.
Методичний підхід щодо визначення рівня сприятливості зовнішнього середовища до розвитку підприємств
Keywords: enterprise management; development; innovation-investment environment; favorableness level; integral assessment; управління підприємством; інноваційно-інвестиційне середовище; рівень сприятливості; інтегральна оцінка